Comparative evaluation of carcass composition of FUNAAB Alpha broiler with two exotic broiler breeds - Ojoawo, H.RT.; Ogunpaimo, O.J.; Ilori, B.M.; Wheto, M.; Durosaro, S.; Adebambo, A.O.; Adebambo, O.A. (Nigerian Journal of Animal Science, 2023)
The contribution of local chickens to meat supply in Nigeria is considered appreciable even though they have been poorly exploited. Thus, this study was conducted to compare the carcass performance of FUNAAB Alpha broilers to Arbor Acre and Cobb 500 breeds. A total of 50 FUNAAB Alpha, 50 Arbor Acre and 50 Cobb broilers were reared for a period of 8weeks. Data collected were in percentage to the total dressed weight and Arcsine transformed to be used as absolute data Analysis of variance (ANOVA). The Cobb 500 breed had the highest value for bled, de-feathered and eviscerated weight (1621.64±93.14g, 1533.14±93.37g and 1254.71±80.19g respectively) followed by the Arbor Acre and FUNAAB Alpha breed. However, the FUNAAB Alpha broiler strain had the highest percentage of heart weight (3.12±0.30), empty gizzard weight (2.34±0.10), liver weight (2.45±0.10), thigh weight (11.21±0.21) and the neck weight (5.45±0.09) while Cobb 500 and Arbor Acre broilers showed higher percentage for wing weight (9.73±0.12), leg weight (4.64±0.12) and drum stick weight (10.78±0.13). The study concludes that the FUNAAB Alpha broilers have good potentials for meat production and could serve as an additional source of animal protein for the rural poor in Nigeria.